2016
DOI: 10.1007/s13311-016-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Depletion with CD20 Antibodies as New Approach in the Treatment of Inflammatory and Immunological Events Associated with Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a highly debilitating pathology that has irreversible impacts and results in functional loss. We evaluated the anti-inflammatory and immunologic role of antibody-mediated depletion of B cells through the glycoengineered anti-muCD20 antibody (18B12) in an experimental model of spinal cord compression, in vivo and ex vivo. Intraperitoneal 18B12 was administered at a dose of 30 mg/kg, 1 h and 6 h after SCI, and mice were sacrificed 24 h after trauma. We demonstrated, in vivo, that 18B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“… 220 Antibody-mediated depletion of B cells through the glycoengineered anti-muCD20 antibody (18B12) in a mouse model significantly inhibits the NFκB-dependent production of pro-inflammatory mediators and improves functional recovery after SCI. 221 The therapeutic CD20 antibodies such as rituximab or obinutuzumab may provide a new immunotherapy for the treatment of CNS injury.…”
Section: Immunotherapy At the Adaptive Immune Response After Cns Injumentioning
confidence: 99%
“… 220 Antibody-mediated depletion of B cells through the glycoengineered anti-muCD20 antibody (18B12) in a mouse model significantly inhibits the NFκB-dependent production of pro-inflammatory mediators and improves functional recovery after SCI. 221 The therapeutic CD20 antibodies such as rituximab or obinutuzumab may provide a new immunotherapy for the treatment of CNS injury.…”
Section: Immunotherapy At the Adaptive Immune Response After Cns Injumentioning
confidence: 99%
“…depleted B cells using 18B12 in a murine model of spontaneous autoimmune thyroiditis in young mice to show that the following activation of regulatory T cells inhibited development of the disease in adult mice [ 37 ]. Casili et al showed that 18B12 treatment lessened inflammation and tissue damage in a model of spinal cord injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted on a rodent SCI model indicated that antibodies targeting myelin-associated inhibitors could increase the locomotor function after injury [ 92 ]. Another study administered B-cell-depleting antibodies to control injury-associated inflammation and the treatment was found to subside the inflammation, promote cell survival and reduce hindlimb dysfunction [ 93 ]. Thus, the combination of immunotherapy and MSC treatment may be more effective in treating SCI by suppressing the inflammation and promoting cord regeneration.…”
Section: Novel Biological Therapies For Spinal Cord Injurymentioning
confidence: 99%